G118 Essential ETAT: Feasibility of Short Duration Paediatric Resuscitation Training in a Resource-Limited Setting. (4th June 2013) - Pollock, L; Morar, N; Dyer, B; Kampmann, B; Clarke, E; Anderson, ST
Abstract : Aims: ETAT and ETAT+ training courses provide comprehensive training in paediatric emergency care over 3.5–5 days and have been shown to improve outcome in resource-limited settings. However, the logistics, cost and impact on local service delivery of a five day course may limit training opportunities in some settings. In this context, we aimed to determine whether a shorter, more focused course – 'Essential ETAT'- would be feasible. Methods: Two resuscitation training courses were designed, of one or 2.5 days duration. Both courses were adapted from WHO ETAT and ETAT+ training materials and included practical and lecture-based sessions on triage, cardiopulmonary resuscitation and recognition and management of key paediatric emergencies. Practical sessions in airway management, bag-valve-mask ventilation and intra-osseous needle insertion were included. There were no hospital-based sessions and newborn emergencies were not included. A short manual summarising ETAT guidelines was provided. Participants were nurses and doctors working in primary or secondary care settings in Gambia. Impact on participant knowledge was assessed by pre and post-course multiple-choice test. Participants' evaluation of the course was assessed by structured questionnaire. Results: Nineteen and 22 participants completed the 2.5 and 1 day courses respectively. Participants on both courses showed a significant improvement in post-course test scores using a paired t-test; 2.5 day course mean scores- pre12.42, post 15.63 (p < 0.001); 1 day course mean scores- pre 14.32, post 16.86 (p < 0.001). There was no significant difference in mean post-course scores (p = 0.08) or in mean increase in score post-course (3.21 compared to 2.54, p = 0.4) between participants from the 2.5 day and 1 day courses respectively. Participant feedback from both courses was positive. Conclusions: The comprehensive training offered by ETAT/ETAT+ is of proven benefit. However, in settings where providing such courses is logistically difficult, focused training of shorter duration may offer a pragmatic and potentially cost-effective alternative. We successfully condensed ETAT/ETAT+ training to two courses of shorter duration. 'Essential ETAT' was well received by participants, and a significant improvement in post-course test scores was achieved. Further evaluation at 6 months post course is required to indicate whether knowledge is retained and changes clinical practise.